65-fs Pulses at 2 µm in a compact Tm-doped all-fiber laser by dispersion and nonliearity management - Sun, Biao (2019)
We report a compact ultrafast thulium-doped all-fiber laser delivering 65-fs pulses through nonlinear compression in a dispersion and nonlinearity managed fiber chain. The laser outputs 560-mW, 3.2-nJ pulses with a very broad bandwidth >160 nm at the central wavelength of 1980 nm. Numerical simulation investigates and verifies the formation and evolution of the ultrafast pulse.